RPA alleviates the inhibitory effect of vinylphosphonate internucleotide linkages on DNA unwinding by BLM and WRN helicases - Garcia, Patrick L. (Oxford University Press, 2004)
Bloom (BLM) and Werner (WRN) syndrome proteins are members of the RecQ family of SF2 DNA helicases. In this paper, we show that restricting the rotational DNA backbone flexibility, by introducing vinylphosphonate internucleotide linkages in the translocating DNA strand, inhibits efficient duplex unwinding by these enzymes. The human single-stranded DNA binding protein replication protein A (RPA) fully restores the unwinding activity of BLM and WRN on vinylphosphonate-containing substrates while the heterologous single-stranded DNA binding protein from Escherichia coli (SSB) restores the activity only partially. Both RPA and SSB fail to restore the unwinding activity of the SF1 PcrA helicase on modified substrates, implying specific interactions of RPA with the BLM and WRN helicases. Our data highlight subtle differences between SF1 and SF2 helicases and suggest that although RecQ helicases belong to the SF2 family, they are mechanistically more similar to the SF1 PcrA helicase than to other SF2 helicases that are not affected by vinylphosphonate modifications.